Ultrasound-assisted nitrogen andbBoron codoping of graphene oxide for efficient oxygen reduction reaction - Zhang, M; Tao, H; Liu, Y; Yan, C; Hong, S; Masa, J; Robertson, A; Liu, S; Qiu, J; Sun, Z (American Chemical Society Publications, 2019)
Development of naturally abundant, low cost, and energy-efficient electrocatalysts for the oxygen reduction reaction (ORR) is essential for commercialization of fuel cells. In this work, we report simple ultrasonication assisted synthesis of nitrogen and boron dual-doped graphene oxide (NB/GO) and demonstrate its application as an effective ORR catalyst realizing predominantly 4e- reduction of O2 to OH- in 0.1 M KOH. Enhanced ORR electrocatalysis of the dual B and N codoped GO as opposed to GO singly doped with B or N arises from the synergistic interaction of the boron and nitrogen species. The content and configuration of both N and B dopants can be readily tailored by controlling the ultrasonic conditions, thereby permitting tuning of the ORR activity. Furthermore, the developed NB/GO metal-free catalyst exhibited very promising long-term durability and resistance to methanol poisoning compared to the state-of the art Pt/C catalyst.